Agropolitan Development Strategies in Pujon District, Malang Regency, East Java Province, Indonesia - Diani, Khonita Rahma; Marjono, Marjono; Ciptadi, Gatot (Graduate School, Universitas Brawijaya, 2023)
Agropolitan is one of the regional development concepts used to overcome urbanization caused by development inequality and regional equity. The development of the Pujon District Agropolitan Area is expected to reduce development inequality and poverty levels. This research aims to identify superior commodities, assess sustainability, and develop appropriate strategies for developing the Pujon District into a prosperous Agropolitan area. Quantitative data is used in the research method. Location Quotient (LQ), Multidimensional Scaling (MDS), and SWOT analysis were used to analyze the data. According to the LQ analysis findings, the Pujon District's primary commodities are garlic, potatoes, cauliflower, large chilies, and carrots. Data analysis using MDS on the ecological, economic, socio-cultural, infrastructure, and technology dimensions, as well as the legal and institutional dimensions, reveals that they are